Determining the conductivity for a nonautonomous hyperbolic operator in a cylindrical domain. (15th January 2018) - Beilina, Larisa; Cristofol, Michel; Li, Shumin
Abstract : This paper is devoted to the reconstruction of the conductivity coefficient for a nonautonomous hyperbolic operator an infinite cylindrical domain. Applying a local Carleman estimate, we prove the uniqueness and a Hölder stability in the determination of the conductivity using a single measurement data on the lateral boundary. Our numerical examples show good reconstruction of the location and contrast of the conductivity function in 3 dimensions.